(untitled) (Journal of the College of Languages (JCL), 2020)
The orient culture and heritage has directly influenced ,in a way or another , the literary works which recently have been noted by the oriental Jews inside and outside of Israel. Several Jewish writers, who came from the orient (especially from Iran ), have written their works while influenced by traditions and customs of the Iranian society, in which they were born , lived , and raised, and by the writers who were born in that society and then moved to Israel and lived there as a result of the Zionism and its notorious promises to gather Jewish people from all over the world to establish their national home at the expense of the Palestinian land and people. That final goal was to find a nationality for a dispersed group of people who came from different traditions and customs , ways of expressions and languages, to form a nation. They do not have but religion and Zionism , a set of religious traditions related to worship rituals, and stories about religious heroes and stories voiced by prophets and wisemen which have become proverbs . The latter is looked upon with doubt by many researchers as they think that Jewish people have taken from other nations (Mursi , Folklore and Israelites , p 62 ). Accordingly , it is a necessity to explore this culture with its traditions, customs, and popular beliefs adopted ,in particular from Iran the birthplace of the parents of the Israeli writer and author Dorrit Rabinyan , who is of Judaism religion ,Iranian origin ,and Israeli existence through her novel (Persian Brides). This novel carried customs , traditions, folklore thoughts , and popular culture that influenced the Jews , their thoughts and behavior which still exist in the Israeli society nowadays . It is well known that popular culture is the science that includes beliefs and customs of any nation as long as those beliefs and customs related to the Collective behavior (James Fries, Folklore in the Old Testament p 21). Despite that the author was born and raised in Israel but her novels , as critics see, packed with folkloric and legendry concepts and thoughts as well as popular beliefs which prevailed in the Iranian Jewish society that she knew from her family and Iranian Jews in Israel ; she tried to reflect in her novel focusing on the popular landmarks. תרבות המזרח והמורשת שלו השפיעה ישירות על היצירה הספרותית שפורסמו בשנים האחרונות של המאה הקודמת על ידי יהודי המזרח בארץ ומחוצה לה ... סופרים רבים מהמזרח ובמיוחד איראן כתבו את יצירותיהם הספרותיות שהושפעו מן המנהגים, והמסורת של החברה האיראנית שבה נולדו וחיו, או מי שנולד באיראן ועלו ארצה והתגוררו שם בגלל הציונות העולמית והבטחותיה הנוראות לאסוף את התפוצות היהודיות מזוויות העולם במולדת לאומית על חשבון ארץ פלסטין. המטרה האולטימטיבית היא ליצור זהות לאומית עבור קבוצה מגוונת של אנשים, שמקורם במנהגים, במסורות, בדרכי ביטוי ובשפות שונות, והם נועדו להיות עם, אין דבר שרק דת, ציונות וקבוצת מנהגים דתיים קשורים בטקסים של פולחן. על סונה של הנביאים ושל החכמים הם ביטויים של מהלך פתגמים, אשר חוקרים רבים ספק, הם רואים את היהודים לקחו אותם מן המורשת של עמים אחרים ( د. احمد علي مرسي ، الفلكلور والاسرائيليات ، ص 62 ) . כאן היינו צריכים לחשוף את התרבות הזאת עם מסורותיה, מנהגיה ואמונותיה העממיות, במיוחד בהשאלה מאיראן, מקום הולדתם של הוריה של הסופרת הישראלית דורית רביניאן, עם הדת היהודית, המוצא האיראני והקיום הישראלי ברומנה " סמטת השקידיות בעומריג’אן " שנשא בתוכו את המסורות, האמונות, הרעיונות הפולקלוריים והתרבות העממית שהשפיעו על היהודים, על רעיונותיהם ועל מעשיהם, אשר עדיין קיימים בחברה הישראלית כיום: ידוע כי התרבות הפופולרית היא המדע הקולט את אמונותיו ומנהגיו של עם, כל עוד האמונות והמנהגים הללו נובעים מהתנהגות קולקטיבית( جيمس فريزر ، الفلكلور في العهد القديم ، ص 21 ) . על אף שהכותבת נולדה וגדלה בישראל, הרומן שלה, כפי שמבחינת המבקרים, מלא ברעיונות, פולקלור, מיתולוגיה ואמונות עממיות ששלטו בקהילה היהודית באיראן ( ישראל יעל , בכרך קטן וציורי , עמ’ 12 ) מה שהיא הכירה ממשפחותיה ומהקהילה היהודית האיראנית בישראל וניסתה לשקף מה היא תרבות פופולרית שירשה בקהילה היהודית האיראנית התרכזה ברומן שלה על מונומנטים פופולריים.